2014
DOI: 10.1073/pnas.1401646111
|View full text |Cite
|
Sign up to set email alerts
|

Ethnolinguistic structuring of sorghum genetic diversity in Africa and the role of local seed systems

Abstract: Significance This paper shows that cultural factors play a key role in shaping the genetic structure in sorghum. We present molecular evidence of close associations between sorghum population structure and the distribution of ethnolinguistic groups in Africa. We show that traditional seed-management practices, which have played an important role for survival and expansion of agropastoral groups in the past, still are remarkably resilient to threats to human security. We argue that efforts to strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 54 publications
4
46
1
Order By: Relevance
“…In a previous study, we analyzed the relationship between sorghum genetic diversity patterns and the organization of rural societies at the local scale and found that different ethnolinguistic groups living in the same locality grow different landraces (5). At the country scale, Deu and colleagues (6) observed that sorghum genetic patterns coincide with major ethnolinguistic groups, and similar patterns have been observed at the broader scale of African linguistic families (7,8).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…In a previous study, we analyzed the relationship between sorghum genetic diversity patterns and the organization of rural societies at the local scale and found that different ethnolinguistic groups living in the same locality grow different landraces (5). At the country scale, Deu and colleagues (6) observed that sorghum genetic patterns coincide with major ethnolinguistic groups, and similar patterns have been observed at the broader scale of African linguistic families (7,8).…”
mentioning
confidence: 84%
“…It has been shown to induce human genetic differentiation by limiting gene flows among ethnolinguistic groups (37,38), as well as to maintain cultural differentiation by limiting the dissemination of knowledge and practices between geographically close groups (39,40). In the same way, patrilocal residence and ethnolinguistic endogamy, driving homophilous seed exchanges, explain the relationship between ethnolinguistic diversity and crop diversity patterns that has notably been observed on country and continental scales for sorghum (6,7), pearl millet (41), cassava, and taro (3,42). Thus, considering seed exchanges as major gene flow drivers, the effect of farmers' social exchange networks on crop diversity dynamics can be interpreted in terms of evolutionary forces.…”
Section: Effect Of Residential and Ethnolinguistic Homophily On Seed mentioning
confidence: 98%
“…Seed exchange among farmers of the same ethnic group may have contributed in shaping this genetic structure (Barnaud, Trigueros, McKey, & Joly, 2008;Orozco-RamĂ­rez et al, 2016;Pressoir & Berthaud, 2004). Codiffusion of sorghum with human migration has been demonstrated at Africa-wide scale (Westengen et al, 2014) and at a regional scale in Kenya (Labeyrie, Thomas, Muthamia, & Leclerc, 2016). Durra sorghum in Senegal are grown mainly by the Fulani ethnic group, so the clustering of Senegalese durra with Ethiopian durra ( Figure S2d) and low F ST (0.052) suggest that durra sorghums moved with Fulani people from northeast Africa (Scheinfeldt, Soi, & Tishkoff, 2010).…”
Section: Distribution and Diffusion Of Ethnic Groups In Senegal Inclumentioning
confidence: 99%
“…Lastly, on a wider spatiotemporal scale, past human migrations have also largely contributed to present‐day diversity patterns, as was remarkably highlighted for sorghum across Africa (Westengen, Okongo, et al., ), for the diffusion of banana from New‐Guinea to West Africa (Perrier et al., ), of maize in the Americas (Vigouroux et al., ), and of sweet potato from South America to Polynesia (Roullier, Benoit, McKey, & Lebot, ).…”
Section: Introductionmentioning
confidence: 99%